2021
DOI: 10.3390/pharmaceutics13091339
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evidence of Carrier-Mediated Distribution of Amantadine to the Retina across the Blood–Retinal Barrier in Rats

Abstract: Amantadine, a drug used for the blockage of NMDA receptors, is well-known to exhibit neuroprotective effects. Accordingly, assessment of amantadine transport at retinal barriers could result in the application of amantadine for retinal diseases such as glaucoma. The objective of this study was to elucidate the retinal distribution of amantadine across the inner and outer blood–retinal barrier (BRB). In vivo blood-to-retina [3H]amantadine transport was investigated by using the rat retinal uptake index method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The 2-year phase 3 clinical trial of over 2,000 patients with open-angle glaucoma showed no effects to prevent glaucomatous progression by daily treatment with memantine [ 43 ]. Crossing the BRB is an important factor affecting the efficacy of glaucoma drugs [ 44 , 45 ]. Notably, various tryptophan metabolites have been demonstrated to be able to effectively cross through the blood-brain barrier (BBB) to confer their immunomodulatory effects in CNS [ 10 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year phase 3 clinical trial of over 2,000 patients with open-angle glaucoma showed no effects to prevent glaucomatous progression by daily treatment with memantine [ 43 ]. Crossing the BRB is an important factor affecting the efficacy of glaucoma drugs [ 44 , 45 ]. Notably, various tryptophan metabolites have been demonstrated to be able to effectively cross through the blood-brain barrier (BBB) to confer their immunomodulatory effects in CNS [ 10 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, amantadine exists mostly in the cationic form [ 24 ]. In addition, our previous results indicated that the amantadine transport system is sensitive to cationic compounds [ 5 ]. The present inhibition study ( Figure 2 and Table 1 ) also showed that several cationic adamantane derivatives that have an amino group on the adamantane skeleton (compounds 1 – 3 and 8 ) inhibited [ 3 H]amantadine uptake by TR-iBRB2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compounds 14 (cycloaliphatic amine) and 23 (linear aliphatic amine), but not compound 3 , were used. The IC 50 values of compounds 9 , 14 , and 23 for amantadine uptake were calculated to be 22.6, 67.0, and 55.3 µM, respectively ( Figure 3 and Table 2 ), and these values were smaller than the K m value (70.9 µM) of amantadine [ 5 ]. This result suggests that these compounds interact with the amantadine transport system with higher affinity than amantadine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations